Evaluation of cross-national global market segmentation and strategy: The case of Korean Wave for ASEAN countries - Kim, Sang Mook; Park, Min Jae (Asia Pacific Management Review, 2020)
We perform a cross-national market segmentation and analyze differences in the evaluation of made-in-Korea electronic home appliances and cosmetics based on experience of and emotion towards Korean drama and K-pop. We conducted a survey of consumers in five countries among the Association of Southeast Nations member countries, which have widely accepted the Korean Wave. We identify six market segments across nations, from “Korean Wave evangelists” to “cultural vigilances,” according to the target nation's experiences and emotions regarding the Korean Wave. This study could provide a useful insight into standardizing or localizing marketing programs as appropriate for each market segment's characteristics.
Keywords: Cross-national research; Emotion towards Korean wave; Experience of Korean wave; Global market segmentation; Korean wave; Perceived quality